Improving Higher Education in Malawi for Competitiveness in the Global Economy - Mambo, Michael M. (World Bank, Washington, DC, 2016)
As the Government of Malawi investigates options to expand access to higher education and improve the quality of higher education provision, the objective of this report is to contribute to an improved understanding of the challenges confronted by the higher education sub-sector in Malawi.